Bilateral Spontaneous Twin Tubal Ectopic Pregnancy: Case Report - Priya Pratapan Nair1 , Amruta Chaudhary2, Mrunal Nakade3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Ectopic pregnancy is a condition where the fertilized oocyte gets implanted outside the uterus. Tubal ectopicpregnancy accounts for 95 % of the ectopic gestation. Remaining 5 % involves the ovaries, cervix, cornua,abdominal and scar site pregnancies. Spontaneous ectopic pregnancy occurs when there is no prior infertilitytreatment taken. Bilateral spontaneous tubal ectopic pregnancy is a rare form of ectopic gestation. HerebyI would discuss a case of spontaneous bilateral ectopic pregnancy and its outcome. Case: A 35 years oldgravid 2 abortion 1 with secondary infertility of 13 yrs came to emergency casualty with complaints of lowerabdominal pain, spotting per vagina with giddiness and syncopal attack.Diagnosis: Based on clinical findings of acute anaemia due to internal blood loss and free fluid in thelower abdomen with fullness on forniceal palpation and bulky uterus. Trans abdominal ultrasonography wasconfirmatory in diagnosing bilateral adnexal mass with free fluid in pouch of Douglas.Intervention: Emergency exploratory laparotomy with adequate blood transfusion. Patient recovereduneventfully.Conclusion: Women in reproductive age group with history of amenorrhoea with irregular spotting and acuteabdominal pain with syncopal attack should be managed vigorously keeping in mind ectopic pregnancy soas to have less morbidity and chances of good future pregnancy. Salphingotomy as an alternative methodshould be practiced.